UNIFIED VERIFICATION METHOD OF ELECTROMAGNETIC COMPATIBILITY BETWEEN ROLLING STOCK AND TRAIN DETECTION SYSTEMS - Bialon, A.; Adamski, D.; Furman, Ju. (Science and Transport Progress, 2021)
Purpose. Axle counters are more and more often applied in train detection systems. The wheel sensor is a main part of each axle counter system. In parallel, more and more complex railway vehicles, especially traction ones, are a potential source of interferences influencing the operation of these train detection systems. It is the reason to verify the electromagnetic compatibility (EMC) between the signalling equipment, particularly train detection systems and new vehicles in the process of obtaining the permission for their exploitation. The measurement of interfering magnetic fields generated by vehicles is one of tests to be carried out. Methodology. For the simplification and unification purpose of the applied interference test methods the EN 50238 standard and TS 50238-3 technical specification were developed. The specification defines unified testing procedures. However, it is necessary to verify if it may replace different testing methods used in particular European states. It is the goal of the European research project financed from the TEN-T network resources. Findings and originality. This project is part of the larger project of facilitation and speeding up the ERTMS system deployment. One of nine measurement campaigns planned in the frame of this project was conducted in Poland by Railway Research Institute.